Interreligious Conflict and the Politics of Interfaith Dialogue in Myanmar - Kyaw, Nyi Nyi (ISEAS - Yusof Ishak Institute, 2019)
Amidst successive episodes of interreligious violence in Myanmar between 2012 and 2014, interfaith dialogue emerged as a crucial conflict resolution and prevention mechanism. The 2011-16 Union Solidarity and Development Party administration often indirectly promoted the use of interfaith dialogue to defuse interreligious tensions and conflicts, though its political will was questionable. Various governmental, intergovernmental, and non-governmental actors have engaged in interfaith dialogue, peace, and harmony initiatives in the past seven years.